Impact of Credit Risk in Farm Planning in the Chiang Mai Valley, Thailand: A Multiperiod Risk-Programming Analysis of Credit Reserves - Thani, Pichit (1993)
Theoretical model indicates that credit risk affects farmers 'debt use and, thus, firm organization. An empirical model is set up to test the hypothesis from the theoretical model. The purpose of this study is to examine how credit availability to individual farmers, as evaluated by their lenders, responds to changes in past levels of farm income. Effects of resulting credit risks on optimal farm portfolios, including credit reserves,are then evaluated with different degree of risk aversion coefficients. The data used in this study were obtained from both primary and secondary sources. The historical data series of farmers' in come and supply of credit were elicited from individual borrower record keeping and approved loan request form. Five lenders and 259 borrowers were selected as the sample of the study. Farmers were classified in to the following six groups : severe loss, moderate loss, average conditions, moderate gain, and favourable gain, based on their farm income experienced by the farmer in the preceding year. Thus, the likelihoods associated with the gain and loss conditions are derived with farm income risk parameters used in this study. Results of two-way analysis of variance, where farm income risk were treated as treatments and lenders were treated blocks, indicated that (i) credit appears to be linearly related to past farm income, at the five percent level of significance, (ii) capital credit has a higher variability than operating credit, and (iii) capital credit is more sensitive to change in past farm income than operating credit. These results are consistent with the hypothesis that farmers' credit is positively correlated with changes in level of farm income, although the correlation appears stronger for capital credit than for operating credit. That is, risks associated with credit availability for capital purchases appears to add more to farmers' total portfolio risk than does credit for operating.